A Methodical Plan Towards Smart Economy in New Egyptian Cities - M. Hafez, Reham (EAI Endorsed Transactions on Smart Cities, 2020)
INTRODUCTION: Initial patterns of urbanization world demonstrate differing scenarios in different continents, requiring diverse methodologies, policies, and strategies. The information & communication technology (ICT) leads to the development of the city management and smart economy which does not adhere to borders and nationalities. The Egyptian economy passed through various stages of development in the last few years, the government policy has National Egyptian initiatives towards the Smart Economy. OBJECTIVES: Stand on the structure of the smart economy to draw the path for Egypt’s local economy to evaluate the existing economic state and conclude to a guiding methodology towards the smart economy in new Egyptian cities. METHODS: Analytical approach to investigate "concepts, the smart economy as a pillar of smart city, urban entities, examples of smart economy projects around the world". Cross-analysis between national governmental initiatives in Egypt to support the smart economy and some development indicators in the new cities. RESULTS: The difference in the locations, inhabitants’ nature of new cities, requires various and varied approaches to process towards the smart economy. CONCLUSION: The research proposes an adaptation methodical plan for developing the smart economy concept in New Egyptian cities, this plan depends on the constants, variables, policies on both national & local levels.